Sintesis Model Pembelajaran Discovery Learning Dalam Meningkatkan Hasil Belajar PKn Siswa: Tinjauan Literatur Sistematis - Luh Putu Yudha Budiarti; Dewa Bagus Sanjaya; I Nengah Suastika (Jayapangus Press, 2026)
Civics education in elementary schools continues to face the problem of low student learning outcomes due to the dominance of conventional, teacher-centered learning methods. This study aims to synthesize scientific findings regarding the contribution of the Discovery Learning model toward student Civics learning outcomes. The method used was a Systematic Literature Review (SLR) guided by the PRISMA protocol utilizing Google Scholar, Semantic Scholar, and Scopus databases. The inclusion criteria specified empirical research articles (Classroom Action Research, experimental, qualitative) published between 2019 and 2026 that measured Civics learning outcomes, resulting in 15 selected articles for analysis. Data were analyzed using a qualitative descriptive approach through the stages of data reduction, data presentation, and conclusion drawing. The primary synthesis results indicate that this model consistently enhances cognitive achievements, with classical completion targets exceeding 85% through independent discovery syntax, while simultaneously strengthening affective competencies such as rights-and-obligations awareness and cooperation character. The novelty of this study lies in its comprehensive mapping that integrates cognitive and affective domains in Civics, alongside identifying guided discovery strategies as a solution to time-constraint challenges in the classroom. In conclusion, this literature synthesis confirms that the Discovery Learning model is highly contributive as an alternative, innovative learning model for building independence and improving the quality of Civics learning outcomes in elementary schools.